A Study to Assess Home Health Nurses from a Carative Perspective. Issue 1 (2nd January 2019) - Lechleitner, Rodeen
Abstract: The aging population is steadily rising, resulting in an increased need for in-home healthcare. This study examined the impact of several carative factors demonstrated by home health nurses. Multiple regression was used to examine the impact of the carative factors, measured by the Caring Nurse Patient Interaction Scale (CNPI-70). A total of 77 home health nurses from five home health agencies in Northeastern Pennsylvania participated in the study. The findings indicate that the principles of care theory are widely applied in home health settings. The author recommends that care theory be a focus of educational health programs and future research.